Incorporating a Nodal Reactive Power Pricing Scheme Into the DisCo's Short-Term Operation - Cerbantes, Marcel Chuma [UNESP]; Fernandez-Blanco, Ricardo; Ortega-Vazquez, Miguel A.; Sanches Mantovani, Jose Roberto [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2019)
Distribution networks have undergone fundamental changes driven mainly by the rapid penetration of distributed energy resources. The distributed power sources connected to the distribution wires (often through power inverters) can provide not just active power, but also reactive power support to the grid. Reactive power management is a key aspect that may substantially affect the efficiency and the quality of supply of distribution networks and, as a consequence, the operation of a distribution company (DisCo). This work proposes the integration of an enhanced version of a practical and transparent nodal reactive power pricing scheme into a precise and complete short-term operation model of a DisCo. This model explicitly considers distribution-network-related technical constraints such as dispatchable and intermittent distributed generation units, voltage-sensitive loads, time-varying retail prices, stationary batteries, step voltage regulators, shunt capacitor banks, and demand-related constraints. The resulting model is characterized as a large-scale highly nonlinear and nonconvex program with continuous, binary, and discrete variables. To solve such problem, a pseudo-dynamic Tabu Search-based algorithm is proposed and effectively tested.
Keywords: DisCo; nodal reactive power pricing scheme; short-term operation; Tabu Search; voltage-sensitive loads